Size- and surface chemistry-dependent pharmacokinetics and tumor accumulation of engineered gold nanoparticles after intravenous administration. Issue 3 (11th March 2015) - Wang, Jing; Bai, Ru; Yang, Ru; Liu, Jing; Tang, Jinglong; Liu, Ying; Li, Jiayang; Chai, Zhifang; Chen, Chunying
<x xml:space="preserve">Abstract</x> It is important and essential to study the pharmacokinetics and biodistribution of gold nanoparticles for safer and more efficient therapeutic purposes.